Careful in the Crisis? Determinants of Older People's Informal Care Receipt in Crisis‐Struck European Countries. (November 2016) - Costa‐Font, Joan; Karlsson, Martin; Øien, Henning
Abstract: Macroeconomic downturns can have an important impact on the receipt of informal and formal long‐term care, because recessions increase the number of unemployed and affect net wealth. This paper investigates how the market for informal care changed during and after the Great Recession in Europe, with particular focus on the determinants of care receipt. We use data from the Survey of Health, Ageing and Retirement in Europe, which includes a rich set of variables covering waves before and after the Great Recession. We find evidence of an increase in the availability of informal care after the economic downturn when controlling for year and country fixed effects. This trend is mainly driven by changes in care provision of individuals not cohabiting with the care recipient. We also find evidence of several determinants of informal care receipt changing during the crisis – such as physical needs, personal wealth, and household structures. Copyright © 2016 John Wiley & Sons, Ltd.